Persepsi Mahasiswa Jurusan Akuntansi Reguler Dan Non Reguler tentang Pendidikan Profesi Akuntansi - Icuk Rangga Bawono; Mochammad Novelsyah; Arum Lutfia (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2006)
The objective of this study is to examine the perception of regular and non-regular undergraduate students majoring in accounting about Pendidikan Profesi Akuntansi (PPAk). It is also to know wheter any difference perception about PPA between regular student of S1 accounting with non-regular student. Respondents consist of 365 regular students and 77 non-regular students of accounting major. All data were processed previously with validity test (Pearson moment) and reliability (Alpha Cronbach). The Result of this research indicates that undergraduate students of accounting major have positive perception about PPAk. There is difference perception between regular and non-regular student about Pendidikan Profesi Akuntansi (PPAk).Keywords: Pendidikan Profesi Akuntansi (PPAk), positive perception, difference perception, regular student of S1 accounting, and non-regular student of S1 accounting